Renal replacement therapy-requiring acute kidney injury due to tubulointerstitial nephritis and uveitis syndrome: case report - Marahrens, B.; Amann, Kerstin Ute; Asmus, K.; Erfurt, S.; Patschan, D. (Journal of Medical Case Reports, 2021)
Background: Acute kidney injury is a major challenge for today’s healthcare systems around the globe. Renal replacement therapy has been shown to be beneficial in acute kidney injury, but treatment highly depends on the cause of the acute kidney injury. One less common cause is tubulointerstitial nephritis, which comes in different entities. A very rare type of tubulointerstitial nephritis is tubulointerstitial nephritis and uveitis syndrome, in which the patient presents with additional uveitis. Case presentation: A 19-year-old caucasian male presented with mild dyspnea, lack of appetite, weight loss, and moderate itchiness. Lab results showed an acute kidney injury with marked increase of serum creatinine. The patient was started on prednisolone immediately after admission. As the patient in this case showed symptoms of uremia on admission, we decided to establish renal replacement therapy, which is unusual in tubulointerstitial nephritis and uveitis syndrome. During his course of dialysis, the patient developed symptoms of sepsis probably due to a catheter-related infection requiring intensive care and antibiotic treatment, which had to be terminated early as the patient developed a rash. Intensified immunosuppression, combined with antibiotics, significantly resolved excretory kidney dysfunction. Conclusions: Since both the primary inflammatory process and the secondary infectious complication significantly impaired excretory kidney function, kidney function of younger individuals with new-onset anterior uveitis should be monitored over time and during follow-up.
CRIS-Team Scopus Importer:2021-12-31
Keywords: AKI; Case report; Interstitial nephritis; RRT; TINU syndrome